2022
DOI: 10.3389/fpsyt.2022.1057915
|View full text |Cite
|
Sign up to set email alerts
|

Goal planning in mental health service delivery: A systematic integrative review

Abstract: IntroductionGoal planning is routinely employed in mental health service delivery to identify priorities for treatment and support the achievement and evaluation of outcomes. Previous systematic reviews of the literature have focused on the use of goal planning in a range of physical and cognitive disability settings, but there is a lack of information regarding how goal planning is used in mental healthcare.AimsThis systematic integrative review aimed to understand the types of goals, effectiveness of goal pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…For the most part, service user experiences aligned with many aspects of goal planning theory, 39 including that goals motivated people to enact changes through increasing attention and effort, and progress was moderated by feedback, commitment, knowledge and ownership. Study findings also highlighted that person‐centred goal planning is an essential element in supporting behavioural change for people experiencing SPMIs and can potentially improve the health of service users 40 …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…For the most part, service user experiences aligned with many aspects of goal planning theory, 39 including that goals motivated people to enact changes through increasing attention and effort, and progress was moderated by feedback, commitment, knowledge and ownership. Study findings also highlighted that person‐centred goal planning is an essential element in supporting behavioural change for people experiencing SPMIs and can potentially improve the health of service users 40 …”
Section: Discussionmentioning
confidence: 93%
“…Study findings also highlighted that person-centred goal planning is an essential element in supporting behavioural change for people experiencing SPMIs and can potentially improve the health of service users. 40 Participative approaches to goal planning were significant, with goal planning providing both a purpose to relationship building and a means to enhance relationships. Pharmacists highlighted the importance of learning about service users and their lived experiences of SPMIs, confirming previous research that found improved outcomes result from goal-planning interventions that develop strong working alliances and listen to service user priorities.…”
Section: Individualised and Flexible Processesmentioning
confidence: 99%
“…Six of the identified tools were described and studied in five or more articles. These included Goal Attainment Scaling including Goal Attainment Scaling for Major Depressive Disorder and Goal Attainment Scaling for Upper Limb Spasticity 2857,113,114,118143,150,172,181 ( n = 61), Canadian Occupational Performance Measure 6,2527,101,103…”
Section: Resultsmentioning
confidence: 99%
“…Effective goal‐setting has been identified as a robust factor in increasing well‐being, strengthening rapport and alliance in therapeutic relationships, and promoting recovery for individuals experiencing mental ill health (Clarke et al, 2009; Smith et al, 2011). Indeed, goal setting and attainment are identified as integral features of recovery (Stewart et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…promoting recovery for individuals experiencing mental ill health (Clarke et al, 2009;Smith et al, 2011). Indeed, goal setting and attainment are identified as integral features of recovery (Stewart et al, 2022).…”
mentioning
confidence: 99%